Medical high-frequency ultrasound imaging using Golay-coded pulse excitation - Zhou, Sheng; Wang, Xiaochun; Ye, Qingsheng; Yang, Jun; Ji, Jianjun; Wang, Yanqun (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
This paper combined the coded excitation with the technique of ophthalmic high-frequency ultrasonic imaging, and proposed a new high-velocity data detection and signal processing method. 16-bit Golay complementary sequences were produced by FPGA, which excited the probe to produce ultrasonic waves. Data detection circuit achieved the digitalized of the 15 MHz high-frequency ultrasonic echo signals in real time. Sampling rate was 120MHz, and sampling bit was 14 bit. Decoded compression arithmetic was realized by FPGA in real time, in which A code compression was alternated with B code compression. The return echo was correlated with the corresponding decode filter A and filter B respectively, and then the echo was delayed and summed to complete the decoding process. The experiment indicated that coded excitation can effectively increase the range of mainlobe and decrease the range of sidelobe. This technique can effectively raise the signal-to-noise ratio, and has significant research value in advancing the ophthalmic ultrasonic image quality and raising the safety of the equipment.